Ekstrakurikuler Tari Untuk Penguatan Karakter Cinta Tanah Air - Nanda Eka Kumala; Apri Irianto; Triman Juniarso (Universitas Negeri Surabaya, 2019)
This research was motivated by the character crisis that occurred in the community. One of the character crises was caused by the low love for the country. The purpose of this study was to describe the implementation and constraints experienced in strengthening the character of love for the country through dance extracurricular activities at Tenggilis Mejoyo 1 Elementary School Surabaya. This study uses a qualitative approach. The data in this study were obtained from the results of observations, interviews, and documentation. The data sources are informants consisting of principals, extracurricular dance teachers, and students, activities, places, and documentation. The data analysis technique is the Miles and Huberman model. The data validity technique is source and time triangulation. The results of this study are not all students of class I-III follow the extracurricular dance well, while the selected students try to follow extracurricular dance well according to the established indicators of love for the motherland. In this study it can be concluded that the implementation of strengthening the character of the love of the homeland through dance extracurricular activities at Tenggilis Mejoyo 1 SDN Surabaya runs in accordance with the established indicators and the obstacles experienced are not too large